2005
DOI: 10.1111/j.1472-765x.2005.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the stability of sacB transcript improves levansucrase production in Bacillus subtilis

Abstract: Aims: To develop a strategy to increase the stability of transcripts of structural genes expressed under the control of sacR, the leader region of Bacillus subtilis levansucrase gene. Methods and Results: Insertion of Shine Dalgarno like sequences in the 5¢-untranslated sacR region controlling the expression of sacB. Depending on the number of stabilizing sequences inserted and the position of these sequences with respect to the translation start codon, it was observed that the mRNA stability and the final pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, a study has reported a way to improve stability of the endogenous sacB transcript by insertion of Shine-Dalgarno like sequence in the 5 0 -untranslated region. 30 This approach resulted in an enhanced production of extracellular levansucrase in B. subtilis. Along with the present result, it suggests that a strategy by stabilizing the gene transcript might be equally useful for enhanced production of either endogenous or heterologous proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a study has reported a way to improve stability of the endogenous sacB transcript by insertion of Shine-Dalgarno like sequence in the 5 0 -untranslated region. 30 This approach resulted in an enhanced production of extracellular levansucrase in B. subtilis. Along with the present result, it suggests that a strategy by stabilizing the gene transcript might be equally useful for enhanced production of either endogenous or heterologous proteins.…”
Section: Discussionmentioning
confidence: 99%